Some effects of submarine pipeline construction on the sessile zoobenthic community of Redang Island - Rezai, Hamid; Ibrahim, H.M.; Idris, B.A.G.; Kushairi, M.R.M. (Springer, 1999)
A submarine pipeline, constructed in 1997-1998 to provide water to Redang Island, Malaysia traverses an area covered with corals. Biological studies were conducted before and following pipeline construction to monitor the changes in the biota at selected sites. Benthic invertebrates (including corals) were used as monitoring tools. Student's t-test and one-way ANOVA macroinvertebrates in pre- and post-construction analyses revealed that there was no significant difference in total abundance of sessile periods. Student's t-test revealed that there was a significant difference in mean of live coral coverage during pre and post-construction periods. There was no apparent change in total numbers of macroinvertebrates. Our results suggest only short-term impacts and recovery of the benthic community.